Effect of Adding Methionine Hydroxy Analogue as Methionine Source at the Commercial Requirement Recommendation on Production Performance and Evidence of Ascites Syndrome of Male Broiler Chicks Fed Corn-Soybean Based - Bunchasak, Chaiyapoom; Sooksridang, Takawan; Chaiyapit, Ratchadaporn (International Journal of Poultry Science, 2006)
An experiment was carried out to determine effects of adding liquid DL-methionine hydroxy analog free acid (LMA) as source of dry DL-methionine (DLM) on growth performance, carcass quality and incidence of ascites syndrome during 0-6 weeks of age. Nine hundred commercial male broiler chicks (ROSS strain) were used. The chicks were divided into 6 groups; each group consisted of 6 replications of twenty five chicks each, and the chicks were kept in floor pens. Water and feed were offered ad libitum throughout the experiment. The following six experimental diets were provided: 1) corn-soybean based diet deficient in methionine, 2) corn-soybean based diet deficient in methionine added with DLM to meet its requirements 3) the first group added with LMA at 88% bioefficacy compared to DLM of the second group 4) the first group added with LMA at the 84% bioefficacy 5) the first group added with LMA at the 80% bioefficacy and 6) the first group added with LMA at the 76% bioefficacy. The results showed that during the starter period, weight gain of chicks fed LMA or DLM were significantly heavier than chicks received methionine-deficient diet (P< 0.01), whilst addition of LMA at 88% bioefficacy of DLM slightly improved weight gain higher than the DLM group. Adding DLM or LMA significantly improved feed conversion ratio (FCR) and percentage of uniformity (P< 0.01). No significant differences were found between supplementing DLM and various LMA on these parameters. During the grower period (3-6 weeks of age), weight gain, FCR, uniformity and feed intake of chicks that received diet supplemented with DLM or LMA were superior to the methionine-deficient group (P< 0.01). Outer breast meat yields was significantly improved (P< 0.05) and abdominal fat slightly decreased when methionine sources were added, while adding LMA at 80% bioefficacy of DLM tends to promote edible meat growth more than the other groups. As for incidence of ascites syndrome, significant effects of methionine sources on heart characteristic and hematocrit value were not seen, but adding methionine significantly depressed plasma triiodothyronine (T3) (at 21 days of age) and seemed to increase plasma uric acid level. This suggests that LMA is an acceptable source of methionine for broiler chicks fed corn-soybean meal diets from day-old to market weight, if maximal growth performances are used as response criteria concerning commercial methionine requirements recommendation. Moreover, antagonistic effect of T3 and uric acid in plasma due to methionine supplementation may be a key factor to eliminate occurrence of ascites syndrome in high productive chicks.